Efficient removal of ibuprofen from aqueous solutions using silica-based nanocomposites: A comparative study - Laila A. Khalil; Mohammed H. Al-Jabari; Saleh M. Sulaiman (Adsorption Science & Technology)
This study investigates the efficacy of environmentally friendly silica-based nanocomposites, SiO 2 -Fe 3 O 4 and SiO 2 -ZnO, for removing Ibuprofen (IBU) from aqueous solutions. The synthesized nanocomposites were characterized using various techniques, such as SEM, TEM, EDS, and FTIR. The adsorption capabilities of IBU onto these nanocomposites were explored through comparative analysis, focusing on factors such as pH, initial pollutant concentration, contact time, and temperature. Results reveal that the adsorption process is pH-dependent, and the lower pH levels enhance the adsorption process. The IBU removal process is faster with SiO 2 -Fe 3 O 4 compared to SiO 2 -ZnO. Kinetic modeling suggests a pseudo-second-order mechanism ( R 2 > 0.99 ) for IBU adsorption onto the surfaces of both adsorbents. Langmuir and Freundlich isotherms were employed and demonstrated to analyze the equilibrium data. The Langmuir model revealed a higher maximum adsorption capacity for SiO 2 -Fe 3 O 4 ( Q max = 59.9 ) than SiO 2 -ZnO ( Q max = 44.2 ) . Thermodynamic analysis indicates a chemisorption mechanism for SiO 2 -ZnO and a physisorption mechanism for IBU molecules on the surface of SiO 2 -Fe 3 O 4 . In addition, the standard thermodynamic parameters for the adsorption process indicate that IBU adsorption via both nanocomposites is exothermic, resulting in reduced entropy, and occurs spontaneously. This research introduces silica-based nanocomposites with Fe 3 O 4 nanoparticles for efficient Ibuprofen removal from aqueous solution. The magnetic properties allow easy separation and reusability, enhancing treatment effectiveness. The study offers valuable insights for improving water treatment strategies with potential industrial applications.